The Development of Paser Recreational Sports (Final Stage) as a New Attraction in the Cacaban Reservoir Tourism Object, Tegal Regency - Ritonga, Dzullfikri; Ali, Mohammad Arif; Pitojo, Abadi; Sahri, Sahri; Anggita, Gustiana Mega; Afghani, Afan; Haidar, Nur Hadziq (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2021)
The development of paser recreational sports (final stage) as a new attraction in the Cacaban reservoir tourist attraction. Judging from the natural resources and characteristics of the Cacaban Reservoir, Tegal Regency, the recreational sport of Paser is very suitable to be raised and developed because it has the potential to make a new attraction in increasing tourist visits. The purpose of this research is to produce a product that did not exist before, so that it can be used as a reference in organizing Paser whether it is recreational or recreational sports activities. Paser is an event that can become a new attraction in Cacaban Reservoir. This research is an umbrella research that uses the Research and Development (RnD) method with a sequence of research stages which are divided into three major stages, consisting of several implementation procedures, namely: 1) Initial stage, 2) Advanced stage, and 3) Final stage (selected focus in this article). The results of this development research indicate that the results of the second stage product expert test scores from the experts can be concluded that the Paser stage II recreational sports book product has an average score of 3.45 which is included in the "Very Eligible" category. The conclusion in this study is the development of recreational sports Paser has the potential to be a new attraction in the Cacaban Reservoir Tourism Object, Tegal Regency.